DETERMINAN PERMINTAAN BATUBARA INDONESIA DI LIMA NEGARA TUJUAN EKSPOR - Puji Lestari, Ni Komang Sri; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
The purpose of this study was to analyze the simultaneous and partial effects of per capita income, exchange rate and population on demand for Indonesian coal exports. Research locations in five export destination countries with data published by BPS, UN Comtrade, World Bank and WTO. The number of observations in this study were 85 observations. Data was collected using non-participatory observation methods. This study uses the method of regression analysis of panel data. The results of regression testing on panel data show that the most appropriate model is FEM. The results showed that per capita income, exchange rate and population variables simultaneously had a significant impact on the demand for coal exports in Indonesia. In part, per capita income and population variables have a positive and significant effects, while exchange rates have non-positive and significant effects on demand for Indonesian’s coal exports. The Indonesian government can expand the market to countries with high per capita income, to increase purchasing power and consumption in destination countries. Considering the exchange rate of foreign currencys against the rupiah, the exchange rate of rupiah against foreign currency should be kept stable, this will make export prices more competitive in the international market and increase coal exports.